Development of a Case Based Learning (CBL) Model Based on a Knowledge Management System to Improve Students' Critical Thinking Skills - Ali, Gunawan; Hasibuan, Anggy Qurnia Raafi; Vitriani, Vitriani; Amril, Amril (AL-ISHLAH: Jurnal Pendidikan, 2024)
The current era changes the educational situation. There is an urgent need to integrate advanced information technology with innovative teaching models to improve students' analytical thinking skills.It was employed to Vocational High School teachers and students as a learning innovation in the current era.The selection of Vocational High School teachers and students for research is because the researcher focuses on research in the field of vocational education and it is  relevant with the researcher's field of knowledge. This study aims to develop and validate a Case Based Learning model integrated with a Knowledge Management System, designed to enhance critical thinking skills among vocational high school students. The paper applies Research and Development with theADDIE scheme. The latest concept of the model, namely the Case Based Learning Model, can be collaborated with the Knowledge Management System to improveCritical Thinking Skills student as a competency needed in the current era. It is expected to have a positive impact and change practices and learning outcomes in the context of the industrial revolution currently taking place.